Anurans Composition and Structure in La Cangreja National Park, Puriscal Municipality (San José, Costa Rica) (Biocenosis, 2021)
Massive disappearances of anurans in Costa Rica are a real problem. These individuals have been affected by habitat loss, climate change, and skin diseases. Likewise, Costa Rica has a great wealth of anuran species that are affected by all the aforementioned problems. It is very important to know the structure and composition of the anuran communities to have control over possible effects that they may suffer. La Cangreja National Park has an important representation of anurans. To get to know the structure and composition of the species present in this park, a total of 52 transects divided into 13 points throughout the park were drawn. Thanks to this, a total of 71 individuals from 7 families of anurans were found. These individuals are divided into a total of 14 families of anurans. On the other hand, the wealth estimators indicate that a maximum of 17 species of anurans can be found in this number of sampled points. Considering the sampling design and the number of historical species in La Cangreja National Park, it can be estimated that 53.84% of the species present at the site were found.
Keywords: anurans; composition; La Cangreja National Park; species; structure